Entomopathogenic Fungi, Isolated From Soils and Bemisia tabaci (Hemiptera: Aleyrodidae) Adults, to Manage the Eucalyptus Red Gum Lerp Psyllid Glycaspis brimblecombei (Hemiptera: Aphalaridae) - Domingues, Maurício Magalhães [UNESP]; Dos Santos, Paula Leite [UNESP]; Gêa, Bianca Cristina Costa [UNESP]; De Carvalho, Vanessa Rafaela [UNESP]; De Oliveira, Fabricio Naka [UNESP]; Soliman, Everton Pires; Serrão, Jose Eduardo; Zanuncio, Jose Cola; Zanetti, Ronald; Wilcken, Carlos Frederico [UNESP] (Oxford University Press (OUP), 2022)
The parasitoid Psyllaephagus bliteus Riek (Hymenoptera: Encyrtidae), entomopathogenic fungi, and chemical insecticides are the main strategies to manage the eucalypts pest Glycaspis brimblecombei Moore. The objective of this study was to isolate and to identify entomopathogenic fungi, collected from Bemisia tabaci Gennadius adults in soybean and tomato crops, and from soil samples in eucalypts, soybean, and native forest areas to evaluate their potential to manage G. brimblecombei. Twelve Beauveria and Cordyceps isolates were selected and compared with the commercial products Boveril Beauveria bassiana Bals. (Hypocreales: Cordycipitaceae), Metarril Metarhizium anisopliae Metschn. (Hypocreales: Clavicipitaceae), and Octane Cordyceps fumosorosea Wize (Hypocreales: Cordycipitaceae) and their respective strains. The fungal isolates were diluted in 0.1% aqueous Tween 80 at a concentration of 1.0 × 108 conidia/ml and sprayed on the G. brimblecombei nymphs with or without lerps. Pest mortality was higher and the TL50 and TL90 lower with the isolates LCBPF 11 C. javanica Frieder. & Bally (Hypocreales: Cordycipitaceae), LCBPF 12 (C. fumosorosea), and LCBPF 67 (C. fumosorosea) from B. tabaci adults. Fungi of the genera Beauveria and Cordyceps developed and caused high mortality of G. brimblecombei nymphs with lerps. The B. bassiana, C. cateniannulata Liang (Hypocreales: Cordycipitaceae), C. fumosorosea, C. javanica, and M. anisopliae isolates showed potential to manage G. brimblecombei. The lerp of this insect enhances entomopathogenic fungus development as a source of inoculum accelerating G. brimblecombei nymph mortality. Entomopathogenic fungi isolated from insects and soils are effective against G. brimblecombei and the presence of the lerp of this insect increases the effectiveness of its control.
Keywords: Beauveria bassiana; Bemisia tabaci; biological control; Cordyceps sp; Metarhizium anisopliae